A novel numerical model to simulate acoustofluidic particle manipulation - ŞİŞMAN, ALPER (IOP PUBLISHING LTD, 2020)
Acoustofluidic systems are attracting more attention in recent years because of their specifications, like versatility, high biocompatibility, high controllability, and simple design. However it is important to optimize the system parameters, which affects system performance. Simulation techniques have a crucial role in optimization since high fabrication costs limit the number of runs. However, the complex Multiphysics structure of the system makes the optimization process very elaborate. Here, an innovative and feasible numerical method to simulate and optimize the acoustofluidic particle manipulation process is reported. The proposed numerical method consists of three main steps. In the first step, surface acoustic waves are generated and propagated on a piezoelectric substrate. Next, the particle motion under the effect of the acoustophoresis force is simulated using successive two-dimensional models representing the different regions along the microfluidic channel. Finally, the particle trajectory is calculated using the superposition method. The proposed numerical method was validated using a reference experimental study available in the literature. The proposed method successfully simulated the separation of particles with diameters of 10 and 15 mu m. This numerical method can be used as an optimization tool for acoustofluidic particle manipulation systems.
Keywords: acoustofluidics; focused surface acoustic waves; particle separation; 3D model; simulation; RADIATION FORCES; TUMOR-CELLS; SEPARATION; MICROSPHERES; DEVICES; DRIVEN